2011
DOI: 10.2989/16085906.2011.637737
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of disclosure and antiretroviral treatment adherence in a South African mining workplace programme and implications for HIV prevention

Abstract: Social and psychological barriers to the disclosure of one's seropositive HIV status to significant others and poor adherence to taking medications pose significant challenges to the scaling-up of access to antiretroviral treatment (ART) in the workplace. Such barriers are predictive of sub-optimal treatment outcomes and bedevil HIV-prevention interventions at a societal level. Against this background, this article explores the lived experiences of 19 HIV-positive male participants, between the ages of 33 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In addition, women provided support to their husbands, even at their own physical and emotional expense, thereby facilitating the maintenance of their husbands' hegemonic behaviours (and traditional masculine position), despite being subordinated by them. In fact, Bhagwanjee et al [61] reported that despite the support rendered by their female partners, most of the men in their study continued to remain unfaithful, thereby actively maintaining their hegemonic masculine position.…”
Section: Living With Hiv: Vulnerability and Invincibilitymentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, women provided support to their husbands, even at their own physical and emotional expense, thereby facilitating the maintenance of their husbands' hegemonic behaviours (and traditional masculine position), despite being subordinated by them. In fact, Bhagwanjee et al [61] reported that despite the support rendered by their female partners, most of the men in their study continued to remain unfaithful, thereby actively maintaining their hegemonic masculine position.…”
Section: Living With Hiv: Vulnerability and Invincibilitymentioning
confidence: 83%
“…For instance, in a study on HIV-positive male mine-workers in South Africa, Bhagwanjee et al . [61] found that participants associated their control over their adherence behaviours with the belief that that they could live a long, healthy and normal life despite their HIV infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outreach programs already have the potential to reach populations with diverse age distributions. These include school-based programs, 25 workplace wellness programs, 26 28 youth centers 29 and programs leveraging health care utilization such as antenatal care 30 and sexually transmitted disease treatment. 31 Age targeting considerations could potentially help to prioritize and justify the expansion of outreach methods that can reach young adults.…”
Section: Discussionmentioning
confidence: 99%